(untitled) (Fiep Bulletin - online, 2014)
SUMMARY: The Chronic Paralysis Brain, currently classified as chronic encefalopatia not gradual espástica (espástica ECNP) has been defined as sequel of a brain aggression that if characterizes, primordially, for an upheaval persistent, but not invariable, of strength, the position and the movement, appearing in first infancy, being directly secondary to a not development injury cerebral, with direct influence in the neurological maturation. This work is destined to explain it and to divulge the contribution of the equoterapia in the moviment of children with espástica ECNP, approaching of that it forms it contributes in the motor stimulation, the results that are being found and the paper of the professional of health in the development of this therapy. For this 60 (sixty) children through questionnaires answered for professionals of health who follow the developed work, in different places of the country had been analyzed. Some analyzed topics had been sex, age, diagnosis and previous time of diagnosis, treatments, parallel treatments, time of equoterapia, initial and current evaluation (presence of cervical balance, of trunk, mental and psychic reactions of protection, alterations), and prognostic. Amongst the results the profit of muscular force was distinguished, of static balance and dynamic, of control of head and trunk, beyond significant alterations in the slight knowledge of corporal project, concluding itself therefore that the multiple equoterapia are an important option of complementary therapy for the carriers of espástica ECNP and deficiencies therefore contributes for one adequate process of whitewashing.